Quantitative and Chromatographic Fingerprint Analysis of Embelia ribes churna Formulations by HPLC Method - Rahul.J, Sudani (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTEmbelia ribes burm f., also known as Vidanga, is one of the oldest herbs in Indian traditional medicine. It is used mainly as an anthelmintic, carminative and stimulants. A selective, precise and accurate High Performance Liquid Chromatography (HPLC) method has been developed for the quantification of Embelin in Vidanga churna formulations. The chromatographic separation was performed on Chromatopak Peerless basic C18 column (250 mm L x 4.6 mm ID Column; packing size- 5µ) with a mobile phase Methanol: Phosphate Buffer pH 3.0 (adjusted with 5% v/v acetic acid) in 90:10 proportion at flow rate was 1.4 ml/min. Densitometric analysis was carried out in the absorbance mode at 291 nm. Developed HPLC method showed good regression (r2= 0.9988 ± 0.0012) and the recovery of Embelin was in the range of 99.6 – 102.2%. The limit of detection and limit of quantitation were found to be 1.94 µg/ml and 5.891µg/ml respectively. The method was validated for precision, recovery, limit of detection and limit of quantitation as per ICH guidelines. The proposed HPLC method was found to be simple, precised and accurate and can be used for the quantitative and chemical fingerprint analysis of Vidanga.